Sintesis Monodiasilgliserol Menggunakan Reaksi Esterifikasi Dengan Katalis Asam - Dyah Tasya; Ida Zahrina; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Mono-diacylglycerol (MDAG) is a type of emulsifier that is widely used in the food and nonfood industries. Monoglycerides are also biodegradable and can be used as additives in food because they provide good effects. Its use can be found in bakery products, foods with low fat content. MDAG can be produced from the esterification process. The advantages of this technique are that the esterification process takes place at a lower temperature than glycerolysis and a shorter time than enzymatic hydrolysis. In the research on the synthesis of mono-diacylglycerol from Palm Fatty Acid Distillate (PFAD) with glycerol, the best results were obtained at a temperature of 150 0C, yielding 74% yield, seeded at 160 0C, the emulsion stability value reached 72% with an ALB level of 39%. At a molar ratio of 1: 2, the MDAG brightness level was 85.57%. Keywords: Gliserol, Mono-diasilgliserol , PFAD